Peran Media Sosial TikTok dalam Meningkatkan Motivasi Belajar Siswa Madrasah Ibtidaiyah - Faris Saputro, Fathan; Putri Azzahra, Sabrina (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2025)
This study aims to explore the impact of using the TikTok application on students' learning motivation at MI Muhammadiyah 2 Solokuro. In contrast to previous findings that highlighted the negative side of social media, this study reveals that TikTok can be used as a fun and effective learning support tool. Using a qualitative descriptive approach and phenomenological method, data were obtained through observation, interviews, and documentation of fifth grade students, parents, and the school environment. The results of the study show that the use of TikTok can increase learning motivation, enrich insight, and stimulate students' creativity. However, on the other hand, excessive use also has the potential to cause dependence and health problems. Therefore, the use of TikTok as a learning medium needs to be done wisely with the supervision of parents and teachers. This study is expected to be a basis for further studies that examine the long-term impacts and quantitative influences of social media in the world of education.